Ketahanan Mortar Di Lingkungan Asam Dengan Berbagai Tipe Semen - Sitompul, Iskandar Romey; Hutapea, Uliarta; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This research study the compressive strength, porosity, weight changes, visual inspection and acidic penetration of mortar OPC cement, mortar PCC cement, and mortar with made by combine of OPC+10% Palm Oil Fuel Ash (POFA). The object test submerge in aquadest, sulfuric acid (H2SO4) with pH 4-5, and peat water. This research result show that the compressive strength increased along with increasing of mortar OPC, mortar PCC and mortar with made by combine of OPC+10% Palm Oil Fuel Ash (POFA) lifes which submerged in aquadest. The compressive strength more decreased, however in mortar PCC cement and mortar with made by combine of OPC+10% POFA have increasing. The porosity test, mortar with made by combine of OPC+10% POFA showed bigger value than mortar OPC and PCC cement. Weigh changes occur with mortar PCC cement when submerged in sulfuric acid and peat water inclined decrease.The mortar PCC cement weight inclined constant. The mortar with made by combine of OPC+10% POFA showed some decreasing but inclined constant. Visual inspection of mortar change become yellow colored when it submerged in peat water. Acid penetration which used phenolphthalein solution showed that mortar OPC cement at 91st day life had onrush by acid effect submerged in sulfuric acid and peat water while the mortar PCC cement and mortar with made by combine of POFA showed more constant condition. Keyword: OPC, PCC, palm oil fuel ash (POFA), sulfuric acid (H2SO4), peat water, aquadest, compressive strength, porosity, weight changes, visual inspection and acidic penetration